2012
DOI: 10.3389/fnhum.2012.00211
|View full text |Cite
|
Sign up to set email alerts
|

Activity in the lateral occipital cortex between 200 and 300 ms distinguishes between physically identical seen and unseen stimuli

Abstract: There is converging evidence that electrophysiological responses over posterior cortical regions in the 200–300 ms range distinguish between physically identical stimuli that reach consciousness or remain unseen. Here, we attempt at determining the sources of this awareness-related activity using magneto-encephalographic (MEG). Fourteen subjects were presented with faint colored gratings at threshold for contrast and reported on each trial whether the grating was seen or unseen. Subjects were primed with a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
(45 reference statements)
4
22
1
Order By: Relevance
“…All those ERP studies showed an increased P3 amplitude in widespread scalp regions in relation to primary visual consciousness (Fernandez-Duque et al, 2003 ; Del Cul et al, 2007 ; Lamy et al, 2009 ; Chica et al, 2010 ), especially when experimental demands did not induce a stimulus expectancy (Melloni et al, 2011 ). In this context, the topographical specificity of our findings was confirmed by magnetoencephalographic (MEG) evidence (Liu et al, 2012 ). That MEG study reported cortical source activity in bilateral occipital-temporal (but not parietal) regions at about 200–350 ms post-stimulus in association with primary visual consciousness of non-spatial stimuli (Liu et al, 2012 ).…”
Section: The Experiments On the Erps Accompanying The Primary Consciousupporting
confidence: 82%
See 1 more Smart Citation
“…All those ERP studies showed an increased P3 amplitude in widespread scalp regions in relation to primary visual consciousness (Fernandez-Duque et al, 2003 ; Del Cul et al, 2007 ; Lamy et al, 2009 ; Chica et al, 2010 ), especially when experimental demands did not induce a stimulus expectancy (Melloni et al, 2011 ). In this context, the topographical specificity of our findings was confirmed by magnetoencephalographic (MEG) evidence (Liu et al, 2012 ). That MEG study reported cortical source activity in bilateral occipital-temporal (but not parietal) regions at about 200–350 ms post-stimulus in association with primary visual consciousness of non-spatial stimuli (Liu et al, 2012 ).…”
Section: The Experiments On the Erps Accompanying The Primary Consciousupporting
confidence: 82%
“…In this context, the topographical specificity of our findings was confirmed by magnetoencephalographic (MEG) evidence (Liu et al, 2012 ). That MEG study reported cortical source activity in bilateral occipital-temporal (but not parietal) regions at about 200–350 ms post-stimulus in association with primary visual consciousness of non-spatial stimuli (Liu et al, 2012 ). The findings of our “visuospatial” experiment corroborated the involvement of parietal and occipital cortex in the primary visuospatial consciousness (Babiloni et al, 2006 ), thus complementing the previous view on the functional role of parietal cortical areas in visuo-spatial attention and consciousness (Driver et al, 2001 ; Chica et al, 2010 ).…”
Section: The Experiments On the Erps Accompanying The Primary Consciousupporting
confidence: 82%
“…In many studies, objective discrimination performance improves dramatically when the stimuli are reported as 'seen' compared with unseen, even when sensory stimulation is identical [23,25,27]. How does the model account for these findings?…”
Section: (B) Discrimination Performance Generally Improves With Subjementioning
confidence: 99%
“…In the last couple of decades, the relationships between brain activity and the contents of perceptual consciousness have been investigated using a variety of experimental techniques operating at different spatial and temporal scales, from single-unit, multi-unit and local field potential recordings in monkeys (Logothetis and Schall, 1989; Leopold and Logothetis, 1996; Wilke et al, 2006; Maier et al, 2007; Wilke et al, 2009), to non-invasive neuroimaging techniques such as EEG, MEG and fMRI in humans (e.g., (Tong et al, 1998; Grill-Spector et al, 2000; Dehaene et al, 2001; van Aalderen-Smeets et al, 2006; Liu et al, 2012; Schurger et al, 2015)) (see (Rees et al, 2002; Tononi and Koch, 2008; Dehaene and Changeux, 2011; Boly et al, 2013; Panagiotaropoulos et al, 2014) for reviews).…”
Section: Introductionmentioning
confidence: 99%